Analisis Kualitas Produk terhadap Minat Beli dan Dampaknya Pada Keputusan Pembelian Produk Oriflame - Iwan Iwan; Eneng Iviq Hairo; Agus Yulianto (Almana : Jurnal Manajemen dan Bisnis, 2019)
Abstract This research was conducted to explain the influence of partially both directly and indirectly from product quality, purchase interest and purchasing decision variables. This research uses explanatory research. The number of population used was 100 respondents taken using accidental sampling and questionnaires used as data collection methods in this study. This study uses path analysis (path analysis. The results of the analysis show that there is a partially significant effect both directly and indirectly between the variables of product quality on Purchase Interest and Purchasing Decisions. The results of the calculation of the model determination are 93.2%, it explains that the contribution of the model to explain the structural relationship of the three variables studied is 93.2%, while the remaining 6.8% is explained by other variables Keywords: Product Quality, Purchase Interests, and Purchasing Decisions.